Success Stories in Asian Aquaculture - De Silva, Sena S.; Davy, F. Brian; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The stories presented in Success Stories in Asian Aquaculture reflect the unique nature of Asian aquaculture, providing first-time insight into how and why it has become so successful. Overall, the book demonstrates how the resiliency, adaptability, and innovation of small-scale aquaculture farmers have been crucial to this success. It also places aquaculture development in Asia into a wider global context, and describes its relationship to natural systems, social conditions, and economics. The book is unique in its in-depth presentation of primary research on Asian aquaculture, and in demonstrating how aquaculture can have a lasting positive impact on livelihoods, food security, and sustainable development. This book will appeal to a wide range of readers. The introduction and conclusion give an excellent general overview of Asian aquaculture, and the individual case studies provide a wealth of new information for specialist readers. Researchers, development workers, and decision-makers, in particular, will be interested in how the Asian experience might be used to strengthen aquaculture development more generally and in other parts of the developing tropics of Latin America and Africa. Sena S. De Silva is Director General of the Network of Aquaculture Centres in Asia-Pacific and Honorary Professor of Aquaculture and Fisheries Biology at the School Life and Environmental Sciences, Deakin University, Victoria, Australia. F. Brian Davy is Senior Fellow at the International Institute for Sustainable Development in Canada and has over 35 years of experience in the field of aquatic resources.
Aquaculture Successes in Asia: Contributing to Sustained Development and Poverty Alleviation -- Recent Developments in Rice-Fish Culture in China: A Holistic Approach for Livelihood Improvement in Rural Areas -- Shrimp Farmers in India: Empowering Small-Scale Farmers through a Cluster-Based Approach -- Backyard Hatcheries and Small Scale Shrimp and Prawn Farming in Thailand -- Cage Fish Culture: An Alternative Livelihood Option for Communities Displaced by Reservoir Impoundment in Kulekhani, Nepal -- Enhancing Rural Farmer Income through Fish Production: Secondary Use of Water Resources in Sri Lanka and Elsewhere -- Striped Catfish Aquaculture in Vietnam: A Decade of Unprecedented Development -- The Genetic Improvement of Farmed Tilapias Project: Impact and Lessons Learned -- The Role of Exotics in Chinese Inland Aquaculture -- Synthesis and Lessons Learned.
Keywords: Marine sciences; Freshwater; Agriculture; Wildlife; Fish; Marine & Freshwater Sciences; Agriculture; Fish & Wildlife Biology & Management